Current status and future research directions of business intelligence and analytics education: a bibliometric analysis - Zhang, Hengchao; Mohd Thas Thaker, Mohamed Asmy; Hamid, Zarinah; Thas Thaker, Hassanudin Mohd (International Journal of Evaluation and Research in Education (IJERE), 2025)
The growing demand for analytics-skilled professionals in today’s digital economy has led higher education institutions (HEIs) worldwide to offer business intelligence and analytics (BI/BA) programs. However, BI/BA education is still in its early stages, with noticeable curriculum structure and pedagogical methods discrepancies. Thus, this study seeks to comprehensively evaluate BI/BA education research and unveil its evolving intellectual framework. Guided by the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines, it employs a bibliometric analysis of Scopus-indexed BI/BA education research published between 2005 and 2023. Utilizing both VOSviewer and Biblioshiny, the findings revealed that BI/BA education research has surged dramatically since 2018. Researchers based in the United States have been instrumental in advancing this research domain and fostering international research collaborations. Our findings underscored two key emerging research trends: i) Integrating BI/BA knowledge into business and IT programs and ii) Incorporating industry 4.0 (IR4.0) technologies into the BI/BA curriculum. The findings call for more research collaborations with leading BI/BA institutes in the United States and China to leverage their rich knowledge and expertise. Furthermore, HEIs and future researchers shall focus on aligning curricula with the advancing digital technologies to ensure graduates possess a holistic and current skill set.